Pengaruh Kompensasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Pt Pama Persada Nusantara Di Sangatta-Kutai Timur - Kaharuddin Kaharuddin (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2017)
The study tries to identify to what extent compensation and discipline for work performance of employees PT Pama Persada. Analysis model used to prove hypothesis is model analysis multiple linear regression that be analyzed with using statistics computer program package, that is SPSS v. 16.0 for Windows. Furthermore it was conducted examination for validity of data by multikolinieritas test, heteroskedasticity test and autocorrelation test. Result of statistics analysis show that coefficient of the free variables regression, that is involvement  factor in compensation (X1) =  0,059, discipline  (X2) = 0,743, and Constanta equal  to 0,697. Equation  of multiple linear regression is: Y =  0,697  + 0,059 X1 + 0,743 X2            Conclusion that receive that level of influence explained by compensation, discipline are as independent variable impact toward performance of employees PT Pama Persada  equal to correlation  coefficient (R), that is 0,766  and level of depended  performance to second of  free variables above is equal to determination  coefficient value (R2) that is 0,587 or 58,7 %.  The result of analysis F – test indicate that all free variables by together have significant influence toward the performance of employees PT Pama Persada. Variable independent has dominant influence to performance of employees PT Pama Persada is discipline.